Performance Comparison of Parallel Programming Environments for Implementing AIAC Algorithms - Bahi, Jacques M.; Contassot-Vivier, Sylvain; Couturier, Raphaël (Journal of supercomputing, 2006)
AIAC algorithms (Asynchronous Iterations Asynchronous Communications) are a particular class of parallel iterative algorithms. Their asynchronous nature makes them more efficient than their synchronous counterparts in numerous cases as has already been shown in previous works. The first goal of this article is to compare several parallel programming environments in order to see if there is one of them which is best suited to efficiently implement AIAC algorithms. The main criterion for this comparison consists in the performances achieved in a global context of grid computing for two classical scientific problems. Nevertheless, we also take into account two secondary criteria which are the ease of programming and the ease of deployment. The second goal of this study is to extract from this comparison the important features that a parallel programming environment must have in order to be suited for the implementation of AIAC algorithms.